YM155 and BIRC5 downregulation induce genomic instability via autophagy-mediated ROS production and inhibition in DNA repair. (April 2021) - Cheng, Siao Muk; Lin, Tzu-Yu; Chang, Yung-Chieh; Lin, I-Wen; Leung, Euphemia; Cheung, Chun Hei Antonio
Abstract: Activation of autophagy plays a critical role in DNA repair, especially for the process of homologous recombination. Despite upregulation of autophagy promotes both the survival and the death of cells, the pathways that govern the pro-cell death effects of autophagy are still incompletely understood. YM155 is originally developed as an expression suppressant of BIRC5 (an anti-apoptotic molecule) and it has reached Phase I/II clinical trials for the treatment of variety types of cancer. However, the target-specificity of YM155 has recently been challenged as several studies reported that YM155 exhibits direct DNA damaging effects. Recently, we discovered that BIRC5 is an autophagy negative-modulator. Using function-comparative analysis, we found in the current study that YM155 and BIRC5 siRNA both induced early "autophagy-dependent ROS production-mediated" DNA damage/strand breaks and concurrently downregulated the expression of RAD54L, RAD51, and MRE11, which are molecules known for their important roles in homologous recombination, in human cancer (MCF7, MDA-MB-231, and SK-BR-3) and mouse embryonic fibroblast (MEF) cells. Similar to the effects of YM155 and BIRC5 siRNA, downregulation of RAD54L and RAD51 by siRNA induced autophagy and DNA damage/strand breaks in cells, suggesting YM155/ BIRC5 siRNA might also induce autophagy partly through RAD54L and RAD51 downregulations. We further observed that prolonged YM155 and BIRC5 siRNA treatment induced autophagic vesicle formation proximal to the nucleus and triggered DNA leakage. In conclusion, our findings reveal a novel mechanism of action of YM155 (i.e. induces autophagy-dependent ROS production-mediated DNA damage) in cancer cells and show the functional complexity of BIRC5 and autophagy involving the modulation of genome stability, highlighting that upregulation of autophagy is not always beneficial to the DNA repair process. Our findings can aid the development of a variety of BIRC5-directly/indirectly targeted anticancer therapies that are currently under pre-clinical and clinical investigations. Graphical Abstract: ga1